Multifunctional Nanoparticles, Nanocages and Degradable Polymers as a Potential Novel Generation of Non-Invasive Molecular and Cellular Imaging Systems - Masotti, Andrea (Recent Patents on Nanotechnology, 2011)
In recent years, polymeric scaffolds have been used in several biomedical applications for delivery of drugs or other biologically relevant molecules. Polymeric nanostructures display different (and in some cases more powerful) properties respect to bulk materials. This, lead academic researchers and industry to cooperate in developing pioneering nanostructured materials for industrial and biomedical applications. Moreover, the preparation and use of systems with multiple (multifunctional) properties (i.e., bioconjugation with superparamagnetic, fluorescent or targeting molecules) is positioned to become a viable and innovative tool for application in several clinical fields. Other nanostructured systems like nanocages and degradable nanoparticles, are emerging as potential innovative systems that could be exploited as multifunctional delivery vectors. This brief critical review is aimed at collecting and discussing some recent patents dealing with the preparation and use of multifunctional nanoparticles, nanocages and degradable nanoparticles in biomedicine and non-invasive bioimaging applications. Perspectives for a potential use of these multifunctional nanosystems in pediatries have been also discussed.
Keywords: nanocages